2020
DOI: 10.1002/jia2.25612
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of facility‐based HIV self‐testing among adult outpatients in Malawi

Abstract: Introduction: HIV self-testing (HIVST) in outpatient departments (OPD) is a promising strategy for HIV testing in Malawi, given high OPD patient volumes and substantial wait times. To evaluate the relative cost and expected impact of facility-based HIVST (FB-HIVST) at OPDs in Malawi for increasing HIV status awareness, we conducted an economic evaluation of an HIVST cluster-randomized controlled trial. Methods: A cluster-randomized trial was conducted at 15 sites in Malawi from September 2017 to February 2018 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 13 publications
0
32
0
Order By: Relevance
“…Sixteen studies reported on cost in terms of implementation or cost-effectiveness. In African countries, offering HIV-ST generally increased total program costs or cost per person tested compared to standard HIV testing [25,145,204,[213][214][215][216][217][218] due to the higher cost of the testing kit and the added cost from strategies to promote adoption. For example, Mulubwa et al [145]…”
Section: Implementation Costsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sixteen studies reported on cost in terms of implementation or cost-effectiveness. In African countries, offering HIV-ST generally increased total program costs or cost per person tested compared to standard HIV testing [25,145,204,[213][214][215][216][217][218] due to the higher cost of the testing kit and the added cost from strategies to promote adoption. For example, Mulubwa et al [145]…”
Section: Implementation Costsmentioning
confidence: 99%
“…They also found that keeping the price of kits low ensured the cost-effectiveness of the program. Nichols et al [218] found that aside from maintaining kit prices low, ensuring high linkage rates is also important to ensure that HIV-ST programs are cost-saving.…”
Section: Plos Onementioning
confidence: 99%
“…Each negative test was assumed to require 20-minutes of staff interaction time, and each HIVpositive test to require 50-minutes of staff interaction time. 9 Overall PITC staff time was taken as the summation of person-time for the number of positive and negative tests of the total cohort assigned a PITC test across the 12-month period. From the community representative survey, 15% of individuals refused PITC HIV testing when offered.…”
Section: Pitc Staff Timementioning
confidence: 99%
“…Costs are reported in 2018 USD collected as part of a previous facility-based HIVST trial in Malawi. 8,9…”
Section: Scenario Costing and Cost-effectiveness Analysismentioning
confidence: 99%
See 1 more Smart Citation